REPRESENTATION OF STUDENTS’ CRITICAL THINKING IN WRITING: A CRITICAL LITERACY PERSPECTIVE - Nasori Efendi; Aceng Rahmat; Ninuk Lustyantie (English Review: Journal of English Education, 2023)
The goal of this study is to investigate university students’ representation on their critical thinking in academic writing from a critical literacy perspective, in which text is bias and it possesses ideological perspective of writer in expressing social critics, inequality, and power relations. Researchers analyzed 91 argumentative texts writing from Indonesian undergraduate English education students, which were qualitatively assessed using Facione’s HCTSR and LaGuardia’ s CLR rubrics, as well as NVivo 12 Plus software and an integrated theme meaning approach to qualitative content analysis. Researchers discovered that students’ critical thinking skills varied in demonstrating their logical arguments, systematic thinking in reasoning, analysis and evaluation, decision-making, and problem-solving strategies in their academic writing in higher education.